Kebijakan Penghapusan Sanksi Administrasi Perpajakan sebagai Stimulus Peningkatan Penerimaan Negara dari Sektor Pajak (Studi Evaluatif Normatif Kebijakan Perpajakan Nasional) - FC Susila Adiyanta (Administrative Law and Governance Journal, 2018)
Elemination of  tax administration sanction is the government's efforts to expand the number of taxpayers to increase state revenues. Kebijakan penghapusan sanksi administrasi perpajakanis the removal of sanctions facility income tax an individual or entity. The abolition of interest on underpaid tax that can be enjoyed by the people who do not have a Taxpayer Identification Number (TIN) or who already have a TIN on January 1, 2008. With the kebijakan kebijakan kebijakan penghapusan sanksi administrasi perpajakan, the subject of taxes that do not have TIN are encouraged to register as taxpayers. However, government policy as a form of a taxpayer's facility is limited implementation until the end of 2008. Can occur, the program will be constrained if there is still a poor perception and assessment of public service officers who carried out the tax.  Keywords: tax administration sanction, tax revenues